The Shandong mud wedge and post-glacial sediment accumulation in the Yellow Sea - Liu, J. P.; Milliman, J. D.; Gao, S. (Geo-Marine Letters, 2002)
Two well-defined deltaic sequences in the Bohai Sea and in the South Yellow Sea represent post-glacial accumulation of Yellow River-derived sediments. Another prominent depocenter on this epicontinental shelf, a pronounced clinoform in the North Yellow Sea, wraps around the northeastern and southeastern end of the Shandong Peninsula, extending into the South Yellow Sea. This Shandong mud wedge is 20 to 40 m thick and contains an estimated 300 km(3) of sediment. Radiocarbon dating, shallow seismic profiles, and regional sea-level history suggest that the mud wedge formed when the rate of post-glacial sea-level rise slackened and the summer monsoon intensified, at about 11 ka. Geomorphic configuration and mineralogical data indicate that present-day sediment deposited on the Shandong mud wedge comes not only from the Yellow River but also from coastal erosion and local rivers. Basin-wide circulation in the North Yellow Sea may transport and redistribute fine sediments into and out of the mud wedge.
538tcTimes Cited:56Cited References Count:34